Use of Lotteries for the Promotion of Voluntary Medical Male Circumcision Service: A Discrete-Choice Experiment among Adult Men in Tanzania. (May 2019) - Ong, Jason J.; Neke, Nyasule; Wambura, Mwita; Kuringe, Evodius; Grund, Jonathan M.; Plotkin, Marya; d'Elbée, Marc; Torres-Rueda, Sergio; Mahler, Hally R.; Weiss, Helen A.; Terris-Prestholt, Fern
Voluntary medical male circumcision (VMMC) is effective in reducing the risk of human immunodeficiency virus (HIV). However, countries like Tanzania have high HIV prevalence but low uptake of VMMC. We conducted a discrete-choice experiment to evaluate the preferences for VMMC service attributes in a random sample of 325 men aged 18 years or older from the general population in 2 Tanzanian districts, Njombe and Tabora. We examined the preference for financial incentives in the form of a lottery ticket or receiving a guaranteed transport voucher for attendance at a VMMC service. We created a random-parameters logit model to account for individual preference heterogeneity and a latent class analysis model for identifying groups of men with similar preferences to test the hypothesis that men who reported sexually risky behaviors (i.e., multiple partners and any condomless sex in the past 12 months) may have a preference for participation in a lottery-based incentive. Most men preferred a transport voucher (84%) over a lottery ticket. We also found that offering a lottery-based financial incentive may not differentially attract those with greater sexual risk. Our study highlights the importance of gathering local data to understand preference heterogeneity, particularly regarding assumptions around risk behaviors.